2020
DOI: 10.14474/ptrs.2020.9.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of real-time ultrasound imaging for manual lymphatic drainage on breast cancer-related lymphedema in individuals with breast cancer: a preliminary study

Abstract: Objective: Breast cancer-related lymphedema (BCRL) is a major sequela after surgery or radiotherarpy for breast cancer. Manual lymphatic drainage (MLD) is designed to reduce lymph swelling by facilitating lymphatic drainage. This study attempted to determine the histologic changes in the skin and subcutaneous layer, and the immediate effect of MLD in decreasing lymphedema using ultrasound imaging, which is the method used most commonly to eliminate BCRL. Design: A single-group experimental study. Methods: Five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
3
0
2
Order By: Relevance
“…Seven of the 25 selected articles from 2004 to 2022 considered use of DUS in conjunction with therapeutic techniques with the objective of demonstrating the progress or regression obtained during treatment. Seo et al 7 used manual lymph drainage (MLD) as lymphedema treatment method and reported the efficacy DUS during the process. Devoogdt et al 19 suggested that another diagnostic method in conjunction is needed until there is more scientific evidence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven of the 25 selected articles from 2004 to 2022 considered use of DUS in conjunction with therapeutic techniques with the objective of demonstrating the progress or regression obtained during treatment. Seo et al 7 used manual lymph drainage (MLD) as lymphedema treatment method and reported the efficacy DUS during the process. Devoogdt et al 19 suggested that another diagnostic method in conjunction is needed until there is more scientific evidence.…”
Section: Resultsmentioning
confidence: 99%
“…There may be increased protein content in the affected tissues, resulting in chronic inflammation, fibrosis, pain, limited amplitude of movement, and/or paresthesia, in addition to reduced immune function, increasing the risk of local inflammation and infections. [4][5][6][7] It has been demonstrated that lymphedema progresses in the form of a vicious cycle, in which lymphatic stasis provokes development of chronic inflammation, involving uncontrolled macrophage and CD4 + cell response and accumulation of fat, which also promotes chronic inflammation through macrophage infiltration and activation, producing inflammatory cytokines which in turn provoke more lymphatic stasis, reducing lymphatic pumping and increasing capillary filtration. 8 With the objective of improving patients' quality of life, reducing their physical and psychological discomfort, it is essential to conduct a precise diagnosis of the problem to achieve better prognosis and support treatment planning.…”
Section: Introductionmentioning
confidence: 99%
“…Entre os 25 artigos selecionados de 2004 a 2022, sete apresentaram considerações sobre o uso da USD em conjunto com técnicas terapêuticas com o intuito de demonstrar o progresso ou regresso obtido no tratamento. Seo et al 7 utilizaram a drenagem linfática manual (DLM) como método para tratamento do linfedema e relataram a eficácia da USD no processo. Já Devoogdt et al 19 sugerem a necessidade de outro método diagnóstico em conjunto até que haja maior evidência científica.…”
Section: Resultsunclassified
“…Estudos relatam que, em estágios iniciais, o linfedema apresenta-se clinicamente como edema em membro superior em região do braço, ombro, pescoço ou tronco homolateral ao tratamento, consequência da remoção de linfonodos e de vasos linfáticos regionais, causando o comprometimento do sistema linfático local e da drenagem linfática. Pode haver um aumento proteico na região tecidual afetada, resultando em inflamação crônica, fibrose, dor, limitação da amplitude de movimento ou parestesia, assim como em diminuição da função imunológica, o que aumenta o risco de inflamações e infecções locais [4][5][6][7] .…”
Section: Introductionunclassified
“…This leads to functional disabilities and mental problems such as anxiety and depression. Areas with BCRL are reported to have decreased local immune function, result in having a higher risk of infection and inflammation [4] .…”
Section: Introductionmentioning
confidence: 99%